2007
DOI: 10.1002/stc.164
|View full text |Cite
|
Sign up to set email alerts
|

Structural damage detection using nonlinear parameter identification with Tikhonov regularization

Abstract: A sensitivity‐based update of a finite element model is used to determine stiffness reduction factors from measured eigenfrequencies and mode shapes. This is generally an ill‐posed nonlinear problem that needs some regularization. Tikhonov regularization is combined with iterative linearization. Regularization has to be applied before linearization, otherwise the regularization effect depends strongly on the number of iterations. A nonlinear version of the generalized cross‐validation method is used to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 27 publications
0
47
0
Order By: Relevance
“…Specifically, the two measures of fit are given by experimentally identified and estimated mode shapes for the r -th mode. Alternative measures of fit can easily be used and found in literature [18][19][20][21][22].…”
Section: Modal Residualsmentioning
confidence: 99%
“…Specifically, the two measures of fit are given by experimentally identified and estimated mode shapes for the r -th mode. Alternative measures of fit can easily be used and found in literature [18][19][20][21][22].…”
Section: Modal Residualsmentioning
confidence: 99%
“…For the second group, the measure of fit I 2 ðyÞ is selected to represent the difference between the measured and the model predicted mode shape components for all modes. Specifically, the two measures of fit are given by Alternative measures of fit [3,[19][20][21][22] can easily be accommodated in the proposed formulation. In particular, it is straightforward to show that…”
Section: Modal Residualsmentioning
confidence: 99%
“…V. Melicher et al [13] identified the piecewise constant parameter using the standard TR method. In addition, many works are mainly concerned with the identification of load position and load number in nonlinear system using the standard TR method [14][15][16]. However, the standard TR method is not completely perfect; there are some unavoidable limitations and disadvantages: (i) the standard TR method may determine approximate solutions that are too smooth; (ii) the approximate solution may lack many details that the desired exact solution might possess; therefore, it is very necessary to discuss other regularization methods to improve the limitations and disadvantages of the regularization method mentioned above.…”
Section: Introductionmentioning
confidence: 99%